Reflective Practices in Inquiry Learning: Its Effectiveness in Training Pre-Service Teachers' Critical Thinking Viewed from Cognitive Styles - Verawati, N. N. S. P.; Hikmawati, H.; Prayogi, S.; Bilad, M. R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study aims to evaluate the effectiveness of reflective practices in inquiry learning to train pre-service teachers' critical thinking skills viewed from cognitive styles. The quasi-experimental design was conducted with two sample groups given the same treatment at the pretest, reflective-inquiry practice learning, and posttest. Before the pretest, each sample was given GEFT (Group Embedded Figures Test) to determine the sample of the FI (field-independent) or FD (field dependent) cognitive style. Two sample groups were pre-service physics teachers (PPT) at two different universities in Mataram, Indonesia. The measurement of critical thinking employed essay tests. Critical thinking skills data were analyzed descriptively (mean difference scores of pretest-posttest and N-gain analysis) and statistically (independent sample t-test) employing SPSS software. The effectiveness of reflective inquiry learning is measured by increasing critical thinking scores where the minimum posttest has the